Republic of Moldova : Technical Assistance Report-Report on Sectoral Accounts Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
This Technical Assistance report on the Republic of Moldova constitute technical advice provided by the staff of the IMF to the authorities in response to their request for TA. The mission recommended that the National Bank of Moldova (NBM) play the lead role in the production of financial balance sheet statistics (FABS). Coordination of the activities of the agencies involved in the project is key to its success. In addition, the mission recommended that the NBM create a higher level group to act as a monitoring committee. The role of this group should be to ensure that the work of the interagency group is proceeding satisfactorily and on time, and to resolve any conceptual or practical issues that the technical group cannot agree on. It should meet at least twice a year, however, may need to meet more often in the earlier part of the project. The NBM agreed with the plan, which aims to compile and FABS publish annual and quarterly by March 2022. By March 2020, the NBM will generate sector annual financial balance sheet data for the 2015-2018 period using existing data. The report recommends organizing a seminar for compilers, the objective is to explain the goal of FABS, present the challenge and the methodology.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet